A quantitative AOP of mitochondrial toxicity based on data from three cell lines. (June 2022) - Tebby, Cleo; Gao, Wang; Delp, Johannes; Carta, Giada; van der Stel, Wanda; Leist, Marcel; Jennings, Paul; van de Water, Bob; Bois, Frederic Y.
Abstract: Adverse Outcome Pathways (AOPs) are increasingly used to support the integration of in vitro data in hazard assessment for chemicals. Quantitative AOPs (qAOPs) use mathematical models to describe the relationship between key events (KEs). In this paper, data obtained in three cell lines, LHUMES, HepG2 and RPTEC/TERT1, using similar experimental protocols, was used to calibrate a qAOP of mitochondrial toxicity for two chemicals, rotenone and deguelin. The objectives were to determine whether the same qAOP could be used for the three cell types, and to test chemical-independence by cross-validation with a dataset obtained on eight other chemicals in LHUMES cells. Repeating the calibration approach for both chemicals in three cell lines highlighted various practical difficulties. Even when the same readouts of KEs are measured, the mathematical functions used to describe the key event relationships may not be the same. Cross-validation in LHUMES cells was attempted by estimating chemical-specific potency at the molecular initiating events and using the rest of the calibrated qAOP to predict downstream KEs: toxicity of azoxystrobin, carboxine, mepronil and thifluzamide was underestimated. Selection of most relevant readouts and accurate characterization of the molecular initiating event for cross-validation are critical when designing in vitro experiments targeted at calibrating qAOPs. Graphical abstract: Unlabelled Image Highlights: A qAOP for mitochondrial toxicity was calibrated using in vitro data. Data was collected in similar experimental setups in three cell lines. The qAOP was calibrated for two chemicals and was mostly chemical-independent. Validation with eight other chemicals cells was unsatisfactory in four chemicals. Accurate characterization of the molecular initiating event is critical.